Improvement in piezoelectric strain of annealed Ba(Zr0.07Ti 0.93)O3 based ceramics - Parkpoom Jarupoom (2018)
In the present work, effects of annealing time on strain behavior, densification, and microstructure of 2 wt. % B2O3doped Ba(Zr0.07Ti0.93)O3ceramics were investigated. The ceramics were initially sintered at 1150 to 1275°C for 2 h. After sintering, the densest ceramics (1250°C ceramics) were selected for annealing at 1000°C for 4-16 h. An increase in strain level and piezoelectric coefficient was observed after some annealing. High bipolar strain level of 0.48% and high piezoelectric coefficients (d*33) of 603 pm/V were obtained for the 8 h samples. Longer annealing times (>8 h) resulted in reduction of the strain level and piezoelectric value. The change in piezoelectric properties was correlated with the densification and microstructure of the studied samples. © 2013 AIP Publishing LLC.